STRATEGI PEMBINAAN AKHLAK SANTRI DI PONDOK PESANTREN INTERNASIONAL DEA MALELA - Budi Witarto, Arif; Trishuta Pathiassana, Mega (Jurnal TAMBORA, 2020)
Pesantren is a type of based educational institutionreligious. The Dea Malela International Islamic Boarding School is one of thema modern Islamic school and all its students live in Islamic boarding schoolsboarding school. the purpose of this research is to know the strategythe guidance applied by Ustadz to students in Islamic boarding schoolsInternational Dea Malela so that it can become a reference for Islamic boarding schoolsothers in building the morals of students to be better, and to knowsupporting and inhibiting factors in the coaching strategy between ustadz andstudents in instilling moral values. The research method usedin this research is a qualitative method which is the methodsto explore and understand meaning by a number of individuals ora group of people who come from social or humanitarian problems. Resultfrom this research is the coaching strategy carried out at the PondokDea Malela International Islamic Boarding School, namely by implementing discipline,exemplary, simplicity, habituation and multiplying activities that can maximize the potential of each student. For fieldsKepesantrenan PPM Dea Malela has compulsory programs such asQiyamul-Lail, One Day One Verse, Literacy, Dhuha Prayer, Muwajjah (studyevening), Ma'tsuroh (praying together before going to sleep), absence, studyingArabic and English vocabulary, Read al-Qur'an, Halaqoh with WaliFoster care, Public Speaking or speech training.